1999
DOI: 10.1149/1.1391936
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanical Polishing of Polyarylether Low Dielectric Constant Layers by Manganese Oxide Slurry

Abstract: Polishing of low dielectric constant (low k) organic layers of polyarylether (poly‐AE) has been studied. Removal rate of poly‐AE is 52 nm/min in polishing by MnO2 slurry at pressure of 163 normalg/cm2 . This rate is 4.2 times greater than that achieved by fumed silica slurry. This rate increase is due to the enhancement of chemical polishing through employing a chemically active slurry of MnO2 . Removal rate for tantalum nitride (TaN) barrier is 97 nm/min in MnO2 slurry. This rate is much greater than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…When 1 wt% MnO 2 was added to 10 wt% silica, the RRs of SiC were still relatively high at ∼1200 nm h −1 . Since MnO 2 by itself is a good abrasive, oxidizer and was used to polish Cu, SiO 2 , low-K dielectrics films and different types of crystalline SiC films, 22,24,[28][29][30][31] we polished a-SiC wafers with 1 wt% MnO 2 powder alone and found that the RRs were only ∼260 nm h −1 , perhaps due to the reduced abrasive action. These data suggest the possibility of strong interaction between the copper and manganese based additives and the a-SiC surface but also emphasize the need for abrasive action to obtain high RRs.…”
Section: Resultsmentioning
confidence: 99%
“…When 1 wt% MnO 2 was added to 10 wt% silica, the RRs of SiC were still relatively high at ∼1200 nm h −1 . Since MnO 2 by itself is a good abrasive, oxidizer and was used to polish Cu, SiO 2 , low-K dielectrics films and different types of crystalline SiC films, 22,24,[28][29][30][31] we polished a-SiC wafers with 1 wt% MnO 2 powder alone and found that the RRs were only ∼260 nm h −1 , perhaps due to the reduced abrasive action. These data suggest the possibility of strong interaction between the copper and manganese based additives and the a-SiC surface but also emphasize the need for abrasive action to obtain high RRs.…”
Section: Resultsmentioning
confidence: 99%
“…Polishing performance and particle characterization.-The fused silica glass of 18 × 14 × 6.792 mm 3 After the polishing procedure, the glass substrate was cleaned using the ultrapure water solution and then dried off for observation.…”
Section: Methodsmentioning
confidence: 99%
“…The Chemical mechanical polishing (CMP) technology was first put forward in 1965 by Monsanto. [1][2][3] It started as a local and global planarization technology to enhance optical lithography process windows and metal interconnect reliability. 4,5 The yield enhancement brought by CMP, has lead to the widespread acceptance of CMP for state-of-the-art interconnect applications, namely,interlayer dielectric and tungsten plugs 6 over other planarization technologies such as etchback.…”
mentioning
confidence: 99%
“…As manganese oxide has been revealed to have some interesting characteristics, several corresponding studies have been performed. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Some of these studies reported that manganese oxide slurry polishes several materials such as tungsten, copper, SiO 2 , and low dielectric constant materials.…”
Section: Introductionmentioning
confidence: 99%